The Things We Took for Granted... - Nuta, Florian (The Journal of Accounting and Management, 2022)
„Do Androids Dream of Electric Sheep?” asked Philip K. Dick in 1968 a year before Woodstock and the „explosion” of love. Obviously, the dystopian science fiction novel set in a post-apocalyptic San Francisco presents a story way off our reality where androids become fugitives and android psychology becomes a real job. Besides questioning humanity, many dystopian stories are based on denying ordinary things and realities, things that we usually take for granted, like breathing air, drinking water, or seeing the blue sky above.